A comparative study of tribological behavior of Steel and brass under dry sliding condition - Bougoffa, Mohammed Seyf Eddine; Sayah, Tahar (University of Eloued جامعة الوادي, 2018)
The objective of this study is to evaluate the friction and wear behavior of hard steel and brass alloy under dry sliding condition, the tribological behavior was investigated and compared by wear tests, using CSM tribometer. These tests consisted of measuring the wear loss and the friction coefficient of samples. Experiments are conducted at normal load 5 and 10 N, sliding velocity 0.04 and 0.15 m/s. Variations of friction coefficient with the duration of friction at different normal load and sliding velocity are investigated. Results show that the two alloys had similar friction and wear performance, although their grain structures and compositions are different. friction coefficient decreases with the increase of normal load and sliding velocity. On the other hand, it is also found that wear loss increase with sliding distance and their trend curve follows a logarithmic law. Microscopic of worn surfaces for each material were carried out and compared. K
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Tribological behavior, Friction, Wear, sliding distance